2009
DOI: 10.1051/0004-6361/200912646
|View full text |Cite
|
Sign up to set email alerts
|

The environs of the ultracompact HII region G45.45+0.06

Abstract: Aims. G45.45+0.06 is an ultra-compact HII (UCHII) region that has been extensively studied. It is known that G45.45+0.06 is embedded in a complex of UCHII regions, but to date, the surrounding ISM on a larger spatial scale has not been analyzed. Methods. Using data from large-scale surveys, the Two Micron All Sky Survey, GLIMPSE, MIPSGAL, MAGPIS and GRS, we performed a multiwavelength study of a region of about 7 × 7 in the vicinity of G45.45+0.06. Results. We found that the UCHII complex lies on the border of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…In previous studies toward several H II regions (e.g., Zavagno et al 2006;Deharveng et al 2008;Paron et al 2009Paron et al , 2011Pomarès et al 2009;Dirienzo et al 2012), an initial number density of ∼10 3 cm −3 was determined. Alexander et al (2013) Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies toward several H II regions (e.g., Zavagno et al 2006;Deharveng et al 2008;Paron et al 2009Paron et al , 2011Pomarès et al 2009;Dirienzo et al 2012), an initial number density of ∼10 3 cm −3 was determined. Alexander et al (2013) Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Collect and collapse (CC) and radiatively driven implosion (RDI) mechanisms may trigger star formation on the borders of H II regions (Elmegreen 1998). Several pieces of observational evidence have been found supporting these star FITS data cubes for 12 CO, 13 CO, and C 18 O are only available at the CDS via anonymous ftp to cdsarc.u-strasbg.fr (130.79.128.5) or via http://cdsarc.u-strasbg.fr/viz-bin/qcat?J/A+A/559/A113 formation mechanisms (e.g., Zavagno et al 2007;Deharveng et al 2008;Paron et al 2009;Tibbs et al 2012). Therefore, a detailed study of the star-forming regions at various wavebands is necessary to trace the star formation scenario of H II region environments.…”
Section: Introductionmentioning
confidence: 99%
“…Our main BLAST detections corresponding to G045.39−00.76 are associated with a bubble (Churchwell et al 2006), separate from the main clouds of the field, and we therefore omit these sources from the main analysis. A common distance of ∼ 7 kpc (1 • ∼ 0.1 kpc scale) is assumed in the present study (in contrast with those used by previous authors of ∼ 6 and ∼ 8 kpc; e.g., Simon et al 2001;Kraemer et al 2003;Paron et al 2009).…”
Section: Distance Estimationmentioning
confidence: 92%
“…A28 is close to the most active region in the cloud as observed in the MIR (G45.45+0.06 [G45.45]), although from its position and extended morphology the submm emission may also be tracing the compressed and extended molecular gas. G45.45 (also a MYSO candidate in the RMS Survey; e.g., Mottram et al 2010) has been observed to lie in the border of a larger and fainter H II region ∼ 3 ′ in size (G45L; Paron et al 2009). Although this structure is also traced by the BLAST images, it has not been included in our photometry/radio analysis.…”
Section: G4545mentioning
confidence: 99%
“…Taking the distance of ∼4 kpc to Sh2-104 (Deharveng et al 2003), the H II region radius is 4.4 pc. As a rough estimate, n 0 can be determined by distributing the total molecular mass over a sphere (e.g., Zavagno et al 2007;Paron et al 2009;Cichowolski et al 2009;Anderson et al 2015;Duronea et al 2015). The mass of the ring is ∼2.2×10 4 M .…”
Section: Star Formation Scenariomentioning
confidence: 99%